THE INFLUENCE OF SERVICE QUALITY ON THE IMAGE OF THE DESTINATION OF GARUT STATION - Adiatma, Dani; Rukma, Deden Firman Syuyaman (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This study aims to investigate the impact of service quality on destination image at Garut Station. Employing a descriptive and verification method with a quantitative approach, research utilized observational techniques and distributed questionnaires to 100 tourists at Garut Station, selected through accidental sampling. Collected data underwent analysis using Structural Equation Modeling-Partial Least Square (PLS-SEM) to assess the extent of service quality’s influence on Garut Station’s destination image. Findings reveal that service quality significantly contributes to enhancing Garut Station’s destination image. These results have implications for informing strategic formulations by Garut Regency Government, Garut Cultural Tourism Office, and Garut Station management. Specifically, they underscore the importance of prioritizing excellent service quality to bolster and shape the station’s destination image.